Institutii inclusive si extractive in Europa medievala - Adrian DUMITRU (Perspective Politice, 2018)
Can the still-existent economic gap between the two halves of Europe be explained by studying the continent’s medieval past? I argue that the development of feudalism and the different trajectory of this complex web of institutions in Eastern and Western Europe respectively can be a potential explanation on why one half has always been behind the other in terms of economics. For this, I use the framework of inclusive and extractive institutions laid down by Douglass North and Robert Thomas and supplement it with a third type of institutions: non-inclusive ones.